Evolución del estado trófico y estructura del fitoplancton de un lago somero de la Región Pampeana: laguna Sauce Grande (provincia de Buenos Aires, Argentina) - Cony, Noelia Leonor (2014)
Sauce Grande shallow lake is located in the Southwest of the Buenos Aires Province, Argentina, with the river Sauce Grande as both affluent and effluent of it. The aim of this work was to evaluate the trophic state and the characteristics of the phytoplankton community of this shallow lake during an annual cycle. Phytoplankton samples were collected monthly and also physico-chemical parameters were measured. The trophic state of the water body was estimated with Carlson Trophic State Index (TSI) based on chlorophyll a concentration. Bacillariophyta was the algal group most widely represented in number of taxa for the entire studied period. In turn, Cyanobacteria was the dominant group with Synechocystis salina Wislouch as the dominant species. Chlorophyll a concentration ranged between 64.6 and 769.4 mg/m3. The total phytoplankton abundance ranged from 1.6×106 to 5.2×106 ind/ml and the biovolume varied from 9.4×107 to 1.4×109 μm³/ml. The chlorophyll a concentration was significantly correlated with phytoplankton abundance but it was not significantly correlated with biovolume. Besides, Carlson’s TSI (Cl a) ranged from 70 to 97. Accordingly, the Sauce Grande shallow lake was classified as hypertrophic for the studied 2012- 2013 period, whereas the status of the water body was determined as eutrophic for the autumn of 2010.